Challenging the liberal order: the US hegemon as a revisionist power. (6th September 2021) - Chan, Steve
Abstract: Current discourse on International Relations conflates international order and the interstate distribution of power. Many studies fail to clarify the concept of international order or to provide systematic empirical analysis that compares states' conduct in relation to this order. The prevailing tendency relies instead on rhetorical assertion or definitional fiat to attribute revisionist and status-quo motivations to different countries. For example, power-transition theory claims that rising states are typically revisionist, whereas established states are committed to the status quo. This article presents a contrarian view, arguing that the dominant or established state can be a revisionist. This state is not forever committed to those rules and institutions of international order that it has played a decisive role in fostering. Conversely, a rising state is not inevitably bent on challenging the order that has enabled its ascendance. Revisionism is thus not unique to a rising power; moreover, this state is not destined to be a challenger to international order and an instigator of systemic war as typically depicted in the current literature. I advance these propositions in the context of recent conduct by China and the US, suggesting that whereas China has become less revisionist over time (even while its power has increased), the US has become more so especially during the Trump administration. The major impetus challenging the liberal international order has come more from domestic sources in the West than from China.